Spectroscopic and electrochemical properties of di-2-thienyl ketone thiosemicarbazone (dtktsc): electrochemical reactions with electrophiles (H+ and CO2). (10th September 2016) - Bakir, Mohammed; Lawrence, Mark A.W.; Nelson, Peter N.; Conry, Rebecca R.
Graphical abstract: The preparation, spectroscopic, electrochemical, and solid state structural properties of the first thiosemicarbazone derivatives of di-2-thienyl ketone (dtktsc) are reported. Electrochemical measurements revealed electro-polymerization, proton and CO2 mediated reduction, and electro-catalytic decomposition of dtktsc. Highlights: The first thiosemicarbazone derivative of di-2-thienyl ketone, di-2-thienyl ketone thiosemicarbazone (dtktsc) is reported. Spectroscopic and electrochemical measurements on dtktsc revealed strong solvent-compound interaction. Electrochemical reduction of dtktsc is imine based. Electrophile (H + or CO2 ) mediated multi-electron reactions occur on the imine reduction. Voltammetric measurements revealed electrochemical decomposition, and electro-polymerization. Abstract: The first di-2-thienyl ketone thiosemicarbazone (dtktsc) and its di-2-thienyl ketone (dtk) hybrid (dtktsc-dtk) were isolated and characterized from the results of their elemental analyses, spectroscopic measurements and X-ray structural analyses. Spectroscopic and electrochemical measurements disclosed sensitivity of dtktsc to changes in its surroundings. Electronic absorption measurements in protophilic solvents (dmso and dmf) in the presence and absence of a base disclosed deprotonation of the thioamide (NH) proton. Variable temperature 1 H NMR measurements divulged entropy driven exchange of NH and NH2 protons with the residual water protons. X-ray structure analyses confirmed the identities of dtktsc and dtktsc-dtk. Electrochemical measurements on dtktsc in the presence and absence of an electrophile (CO2 or H + ) revealed irreversible redox processes pointing to electrochemical decomposition, reactions with electrophiles and electro-polymerization. On GC-electrode electro-polymerization of dtktsc occurs in CH3 CN on oxidative scans. On reductive scans at a Pt-electrode, electro-catalytic decomposition of dtktsc occurs. Plausible mechanisms for the electrochemical decomposition and reactions of dtktsc with electrophiles are proposed.